(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Lalitha and Tripathi (2018) have suggested a test statistic for the detection of a pair of outliers in a sample from a Gumbel distribution with known scale parameter σ. The statistic is not found to be suitable while dealing with the case of unknown scale parameter σ. Thus, in this paper, the test statistic suggested by Lalitha and Tripathi (2018), is suitably modified by using the modified moment estimator of the scale parameter σ for the detection of two single (upper/lower) outlying observations and one more test statistic is suggested for the detection of a pair of outlying observations. Their critical values and performance probabilities are obtained at different levels of significance by a simulation technique.